Chromosome-Level Genome Assembly and HazelOmics Database Construction Provides Insights Into Unsaturated Fatty Acid Synthesis and Cold Resistance in Hazelnut (Corylus heterophylla) - Liu, Jianfeng; Wei, Heng; Zhang, Xingzheng; He, Hongli; Cheng, Yunqing; Wang, Daoming (Frontiers in Plant Science, 2021)
Corylus heterophylla (2n = 22) is the most widely distributed, unique, and economically important nut species in China. Chromosome-level genomes of C. avellana, C. heterophylla, and C. mandshurica have been published in 2021, but a satisfactory hazelnut genome database is absent. Northeast China is the main distribution and cultivation area of C. heterophylla, and the mechanism underlying the adaptation of C. heterophylla to extremely low temperature in this area remains unclear. Using single-molecule real-time sequencing and the Hi-C assisted genome assembly strategy, we obtained a high-quality chromosome-scale genome sequence of C. heterophylla, with a total length of 343 Mb and scaffold N50 of 32.88 Mb. A total of 94.72% of the test genes from the assembled genome could be aligned to the Embryophyta_odb9 database. In total, 22,319 protein-coding genes were predicted, and 21,056 (94.34%) were annotated in the assembled genome. A HazelOmics online database (HOD) containing the assembled genome, gene-coding sequences, protein sequences, and various types of annotation information was constructed. This database has a user-friendly and straightforward interface. In total, 439 contracted genes and 3,810 expanded genes were identified through genome evolution analysis, and 17 expanded genes were significantly enriched in the unsaturated fatty acid biosynthesis pathway (ko01040). Transcriptome analysis results showed that FAD (Cor0058010.1), SAD (Cor0141290.1), and KAT (Cor0122500.1) with high expression abundance were upregulated at the ovule maturity stage. We deduced that the expansion of these genes may promote high unsaturated fatty acid content in the kernels and improve the adaptability of C. heterophylla to the cold climate of Northeast China. The reference genome and database will be beneficial for future molecular breeding and gene function studies in this nut species, as well as for evolutionary research on species of the order Fagales.